UNDERSTANDING POLITICAL ISLAM MOVEMENTS - Harb, Mustafa (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
This article focuses on political Islam, its emergence, development, principles, and the struggle against liberal movements. It shows the difference between Islam as a religion and as a political movement and points at the difference between Islamic fundamentalism and democratic Islam. Though Islamic movement is based on the common principles, there exist different approaches towards Islamic law and its application in the real world.